A review on different priming strategies to mitigate abiotic stress in plants - Lipun Sahoo; Bharati Swain; Deepanker Yadav (Discover Applied Sciences)
Abstract Abiotic stresses, including drought, salinity, extreme temperatures, and heavy metal toxicity encompassing adverse environmental conditions, poses a significant threat to plant growth, development, and productivity. These stress factors disrupt physiological and biochemical processes in plants, leading to reduce crop yields and posing a threat to global food security. To mitigate the detrimental effects of abiotic stresses, innovative agronomic practices are essential. Different methodologies have evolved over time for stress tolerance through conventional breeding and transgenesis. To enhance plant resilience against these stresses, priming strategies have emerged as a promising tool to improve plant stress tolerance. This review explores various priming approaches that precondition plants to better cope with subsequent stress exposure. Moreover, it discusses the underlying mechanisms involved in enhanced activation of antioxidant systems, improved osmotic balance, regulation of stress-responsive genes, and the strengthening of cellular defence systems. Additionally, priming induces stress memory in plants, enabling faster and more robust responses during recurrent stress events. This review also highlights recent advancements in priming techniques and their potential applications in sustainable agriculture. Integration of these strategies into crop management practices can improve plant performance and productivity in the face of increasing abiotic stresses. Overall, this review provides insights into the efficiency, sustainability, and applicability of different priming strategies as a means to mitigate abiotic stress in plants, offering a promising path toward sustainable agriculture in the face of changing environmental conditions.